Chronicles of eclipsed hope: Dissecting suicide through Sylvia Plath's labyrinthine diaries - Rahmatullah , Mohammad (Global Journal of Social Sciences Studies, 2025)
This study examines the complex relationship between Sylvia Plath's diaries and her reflections on suicidal ideation, comparing her personal narratives with broader epidemiological data on suicide. By analyzing Plath's writings through the lens of Narrative Identity Theory, the research explores the societal and cultural influences that may have exacerbated her psychological struggles. The study employs a qualitative methodology, integrating insights from Plath’s diaries with quantitative data to provide a comprehensive perspective on suicidology. The findings reveal that Plath's diaries serve not only as intimate chronicles of her inner turmoil but also as representations of the broader societal pressures faced by women in the mid-20th century. These narratives highlight the intricate interplay between personal vulnerabilities and external stressors, offering valuable insights into the progression of suicidal ideation. The study advocates for incorporating personal accounts into suicide research to enrich understanding and develop early intervention strategies. Practical implications include the potential for leveraging personal narratives as tools for identifying early warning signs and designing empathetic prevention measures. By focusing on the rich and nuanced details of Plath's diaries, this research underscores the importance of merging qualitative and quantitative approaches to better understand and address the multifaceted nature of suicide.